0364 Insomnia with Objective Short Sleep Duration and Coronary Artery Calcification: Multi-Ethnic Study of Atherosclerosis. (27th April 2018) - Weng, J; Bertisch, S; Lutsey, P; Kaufman, J; McClelland, R; Redline, S
Abstract: Introduction: Insomnia with polysomnographic-short sleep is associated with higher risk of diabetes, incident hypertension and cardiovascular disease (CVD), and mortality. However, there are limited data regarding the relationship between insomnia with polysomnographic-short sleep and subclinical CVD. Moreover, no previous study has examined the association between insomnia with actigraphic-short sleep and CVD. In this context, we examined whether insomnia with objective short sleep, defined alternatively using either polysomnography and actigraphy, is associated with coronary artery calcification (CAC), in a racially/ethnically diverse sample. Methods: Sleep was assessed by polysomnography (PSG), 7-day actigraphy, and questionnaires. Insomnia with short sleep was defined as: self-reported trouble falling or returning to sleep, frequent awakenings, early-morning awakenings, or hypnotic use, for ≥5 nights/week; and total sleep time of <6 hours on single-night PSG or 7-day average from actigraphy. CAC was categorized by CAC=0 vs CAC>0. We employed binomial regression to determine the associations between insomnia with short sleep, using PSG and actigraphy, separately. Results: Our sample of 1, 611 participants were a mean age 68.4 ± 9.2 years, 46.1% male, and 36.4% white, 27.3% African American, 24.1% Hispanic, and 12.2 % Chinese. Among these participants, 48.3 % self-reported insomnia, and of these, 44.1% slept <6 hours during PSG and 30.0% slept <6 hours per actigraphy. CAC (>0) was present in 61.7%. In an unadjusted analysis, insomnia with short sleep was associated with higher prevalence of CAC relative to no insomnia/normal sleep duration (actigraphy, RR 1.29; C.I., 1.16, 1.43; PSG, RR 1.30; C.I., 1.17, 1.45). After adjustment for age, sex, race/ethnicity, education, smoking, physical activity, apnea hypopnea index, and antidepressants, relationships between insomnia with actigraphic-short sleep (RR 1.13;1.02, 1.25) and PSG-short sleep (RR 1.07; 0.97, 1.18) were attenuated. Conclusion: In this large multiethnic cohort, insomnia with actigraphic-short sleep was significantly associated with subclinical CVD. These findings highlight the potential importance of using objective assessments of sleep in patients with insomnia when assessing CVD risk, as well as exploring the role of actigraphy in further defining this vulnerable phenotype. Support (If Any): R01HL098433.